Elementary statistics : a modern approach - Altares, Priscilla S.; Copo, Antonio Roland I.;Gabuyo, Yonardo A.;Laddaran, Angeline T.;Mejia, Leila D.P.;Policarpio, Immaculata A.;Sy, Evangeline Agueda G.;Tizon, Helen D.;Yao, Ana Maria S.D. (Manila, Philippines : Rex Book Store, 2003)
This boo aims to provide college students of business administration, accountancy, and other related courses theories and applications of statistics. It is designed to help students be prepared in their field of interest.
Chapter 1. Introduction -- Chapter 2. Organization and presentation of data -- Chapter 3. Frequency distribution -- Chapter 4. Measures of central tendency -- Chapter 5. Measures of variability -- Chapter 6. Principles of counting and theories of probability -- Chapter 7. Probability and normal distribution -- Chapter 8. Measures of correlation -- Chapter 9. Hypothesis Testing.
Keywords: ACCOUNTING -- STATISTICAL METHOD